An investigation of teacher and teacher candidates’ views on the course of school experience - Emine Begüm Akkuş; Lütfi Üredi (Institute of Advanced Engineering and Science, 2021)
One of the most important elements involved in the development of countries is teachers. Therefore, developing countries should pay attention to training good teachers. Thus, the purpose of this study was to present the opinions of teachers and prospective teachers on the “teaching experience” course. The study is based on a qualitative research. The data were collected from 84 teachers in Şanlıurfa, an eastern city of Turkey and 88 prospective teachers (undergraduate seniors) studying at Mersin University, Turkey. Semi-structured interview form was utilized to collect the required data. Besides, content analysis was applied in the study. The data have been expressed in numbers. Results have displayed that there are problems arising from the stakeholders in the “teaching experience” lesson. The types of schools attending internships are not inclusive. Not all stakeholders are working cooperatively. Moreover, the following suggestions were accordingly put forward: 1) The internship duration can be extended; 2) Applications covering all types of schools should be added; and 3) Stakeholders should be encouraged to work in a collaborative way.